55 High serum parathyroid hormone levels are not associated with endothelial function, vascular stiffness or early adverse outcomes after invasive management of non-st elevation myocardial infarction in high-risk older patients. (5th June 2017) - Beska, Benjamin; Neely, Dermot; Datta, Harish; Gu, Sophie Zhaotao; Batty, Jonathan; Sinclair, Hannah; MacGowan, Guy; Ford, Gary; Qiu, Weiliang; Kunadian, Vijay
Abstract : Introduction: High serum parathyroid hormone (PTH) levels are associated with increased risk of cardiovascular events. Older patients have an increased risk of adverse events after non-ST elevation acute coronary syndrome (NSTEACS) and PTH may be a useful biomarker in these patients. The link between PTH, endothelial function, vascular stiffness and early outcomes after NSTEACS was evaluated. Methods: Older patients (65 years old) referred for invasive management of NSTEACS were recruited into the study (n=204). Serum PTH was measured by electrochemiluminescent immunoassay and split into tertiles for analysis. Vascular stiffness was evaluated with carotid-femoral pulse wave velocity (PWV). Endothelial function was assessed by peripheral arterial tonometry, reported as natural log reactive hyperaemia index. Major Adverse Cardiovascular Events (MACE) were defined as 30 day composite of all-cause mortality, acute coronary syndrome, unplanned repeat revascularisation, significant bleeding, stroke or transient ischaemic attack. Multiple linear and logistic regressions were performed to control for age, sex, hypertension, diabetes, glomerular filtration rate and smoking status. Results: Mean age was 80.7±4.0 years (64.7% male). Median PTH was 5.9 pmol/L [IQR 4.3–7.8 pmol/L] and 81 patients (39.7%) had levels above the normal range (1.1–6.4 pmol/L). There were 83 (40.7%) patients in the high (6.4 pmol/L), 62 (30.4%) in the middle (6.3–4.5 pmol/L) and 59 (28.9%) in the low tertile (4.4 pmol/L) of PTH. There was no difference in mean PWV (high 8.51±1.77 metres per second (m/s); middle 9.89±2.75 m/s; low 9.41±2.09 m/s; p=0.646) or mean natural log reactive hyperaemia index (high 0.64±0.34; middle 0.61±0.23; low 0.59±0.25; p=0.684) between PTH tertiles. There was no adjusted linear relationship between PTH and PWV (p=0.09) or natural log reactive hyperaemia index (p=0.919). MACE incidence did not vary between tertiles (high 2.4%; middle 1.6%; low 3.4%; p=0.819) and adjusting for covariates, PTH was not predictive of MACE (p=0.308). Conclusion: In this high-risk older cohort, high serum PTH levels are not linked with endothelial dysfunction or vascular stiffness and do not predict early adverse events after invasive management of NSTEACS.